The Lived Experience of Indonesian Doctoral Mothers: An Interpretative Phenomenological Analysis - Juliana Irmayanti Saragih; Hari Basuki Notobroto; Fitri Andriani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2026)
Mothers who pursue doctoral study in Indonesia have grown in number alongside the broader expansion of doctoral education. However, how they interpret and make sense of navigating scholarly and maternal responsibilities within their sociocultural context remains largely unexplored. This study employed Interpretative Phenomenological Analysis (IPA) to examine how ten Indonesian doctoral mothers (aged 31–43) constructed meaning around simultaneously inhabiting the roles of scholar and active mother. In-depth semi-structured interviews were analyzed ideographically prior to the development of carefully grounded cross-case interpretations. Five themes emerged. Participants experienced doctoral entry as institutional necessity rather than personal intellectual aspiration, driven by promotion requirements and credential gatekeeping. They described their doctoral journey as walking a narrow rope, balancing demands as doctoral students, academic professionals, and mothers while navigating hierarchical supervisory relationships. Traditional domestic responsibilities persisted unchanged alongside their studies, anchored by cultural understandings of kodrat wanita and reinforced by social surveillance. Profound guilt ran across their daily lives, directed toward their children, spouses, and academic selves. Faith practices, family networks, and peer solidarity functioned as their primary sustaining resources, transforming hardship into meaning through prayer, gratitude, and communal emotional sharing. These findings illuminate how Indonesian doctoral motherhood is shaped by the intersection of institutional demands, gendered cultural norms, and religious meaning-making. The study contributes to more culturally grounded understandings of academic motherhood and calls for institutional responses that recognize the lived complexity of women scholars in collectivist contexts.